Structural, optical and potential sensing properties of tyrosinase immobilized graphene oxide thin film on gold surface - Hashim, Hazwani Suhaila (Elsevier GmbH, 2020)
In this study, spin coating technique has been used for the preparation of tyrosinase immobilized graphene oxide thin film on gold surface. The thin film then was characterized for its structural properties using Fourier transform infrared spectroscopy (FTIR) and atomic force microscopy (AFM), meanwhile the optical properties were studied using Ultraviolet-Visible spectroscopy (UV-Vis). From FTIR results, the presence of functional groups in the thin film have been confirmed and the surface morphology observed by AFM revealed the thin film is homogenous where the surface of graphene oxide is covered by tyrosinase. Besides, the UV-Vis results proved that the thin film has high absorbance value with an optical band gap of 4.082 eV. Moreover, the potential of this modified thin film as a sensing element for phenol detection has been studied using surface plasmon resonance (SPR) technique. The SPR results showed that the thin film has a sensitivity of 0.00234° μM-1 and also the ability to detect phenol down to 1 μM.